Parents’ role in preventing gadget addiction amongst preschoolers living in urban and rural areas: A qualitative study - Fahrizal, Yanuar; Mariyana, Dian Mya; Hasan, Shukir Saleem (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Parents frequently give their children electronic devices without considering the consequences. Most typically do this to calm temperamental children, which increases the risk of detrimental effects. This study aims to investigate how parents manage electronic device usage among preschool children. A qualitative research design using a phenomenological method was used. Ten parents with children aged 3-6 participated, selected by purposive sampling. The data collection methods employed included documentation, in-depth interviews, and observation. The trustworthiness strategy included reflexive journaling during the thematic analysis process, bracketing, peer debriefing, and a participant check procedure. The data analysis methodology used was interpretative phenomenological analysis (IPA). The study findings reveal three main themes: 1) the influence of the nuclear family on children’s use of electronic devices; 2) the behavioral patterns associated with the utilization of electronic devices in preschool children; and 3) parental management of electronic devices among preschool children. It is suggested that nurses and health workers collaborate with parents and other family members to prevent preschool children from developing an addiction to electronic devices. It can be achieved through various strategies, such as establishing rules for playing with gadgets, limiting internet access, determining the duration of gadget play, rewarding or punishing children for achievements or negative behaviors, and redirecting them to physical activities outside the home.